Creation of Model and Calculation of Thermal Processes in the Ring Graphite Electrode of the Plasmatron - T. Nasibullin, Ramil; Sh. Sadriev, Almaz; Sh. Sadriev, Ramil; R. Sarimov, Lenar (International Journal of Engineering and Technology, 2018)
This paper presents the theoretical and experimental material obtained in the study of the erosion and thermal state of the ring graphite electrode for a plasmatron. Thermal processes in graphite electrodes of plasmatrons are quite complex and multifaceted. A mathematical model of thermal processes that occur at the ring electrodes of plasmatrones has been developed. The mathematical model is based on the differential heat conduction equation for a ring electrode in cylindrical coordinates. With the use of this mathematical model, the inverse problem of heat conduction is solved: determination of the regularities of the heat exchange process by the temperatures of individual points on a solid surface. An experimental study of the temperature distribution at the end of the electrode and along the length of the electrode was carried out. Experiments have shown that the temperature on the side surfaces drops sharply towards the cold end of the electrode. When reducing the length of the electrode, the maximum temperature at the end decreases, and the temperature on the inner and outer edges of the electrode increases slightly. The most significant factors determining the temperature field at the end of the ring electrode are the power and size of the heat source. Comparison of the results of experimental studies and mathematical modeling showed a match with an acceptable degree of accuracy.Â Â Â